Trp64Arg polymorphism of the ADRB3 gene associated with maximal fat oxidation and LDL‐C levels in non‐obese adolescents - Íncare Correa de Jesus; Lupe Furtado Alle; Eva Cantalejo Munhoz; Larissa Rosa da Silva; Wendell Arthur Lopes; Luciane Viater Tureck; Katia Sheylla Malta Purim; Ana Claudia Kapp Titski; Neiva Leite (Brazilian Society of Pediatrics, 2018)
Objective: To analyze the association between the Trp64Arg polymorphism of the ADRB3 gene, maximal fat oxidation rates and the lipid profile levels in non-obese adolescents. Methods: 72 schoolchildren, of both genders, aged between 11 and 17 years, participated in the study. The anthropometric and body composition variables, in addition to total cholesterol, HDL-c, LDL-c, triglycerides, insulin, and basal glycemia, were evaluated. The sample was divided into two groups according to the presence or absence of the polymorphism: non-carriers of the Arg64 allele, i.e., homozygous (Trp64Trp: n = 54), and carriers of the Arg64 allele (Trp64Arg + Arg64Arg: n = 18), in which the frequency of the Arg64 allele was 15.2%. The maximal oxygen uptake and peak of oxygen uptake during exercise were obtained through the symptom-limited, submaximal treadmill test. Maximal fat oxidation was determined according to the ventilatory ratio proposed in Lusk's table. Results: Adolescents carrying the less frequent allele (Trp64Arg and Arg64Arg) had higher LDL-c levels (p 0.031) and lower maximal fat oxidation rates (p = 0.038) when compared with non-carriers (Trp64Trp). Conclusions: Although the physiological processes related to lipolysis and lipid metabolism are complex, the presence of the Arg 64 allele was associated with lower rates of FATMAX during aerobic exercise, as well as with higher levels of LDL‐c in adolescents. Resumo: Objetivo: Analisar a associação entre o polimorfismo Trp64Arg do gene ADRB3, as taxas de oxidação máxima de gorduras e as concentrações do perfil lipídico em adolescentes não obesos. Métodos: Participaram do estudo 72 escolares, de ambos os sexos, com idade entre 11 e 17 anos. Foram avaliadas as variáveis antropométricas e de composição corporal, além do colesterol total, lipoproteina de alta densidade, lipoproteina de baixa densidade, triglicerídeos; insulina e glicemia basal. A amostra foi dividida em dois grupos, segundo a presença ou não do polimorfismo: não portadores do alelo Arg64, ou seja, homozigotos (Trp64Trp: n = 54) e portadores do alelo Arg64 (Trp64Arg + Arg64Arg: n = 18), em que a frequência do alelo Arg64 foide 15,2%. O consumo máximo de oxigênio e pico de consumo máximo de oxigênio durante o exercício foram obtidos por meio do teste aeróbio submáximo de sintoma limitado em esteira. A oxidação máxima de gorduras foi determinada de acordo com a razão de trocas ventilatórias propostas na Tabela de Lusk. Resultados: Os adolescentes portadores do alelo menos frequente (Trp64Arg e Arg64Arg) apresentaram maiores concentrações de lipoproteina de baixa densidade (p = 0,031) e menores taxasde oxidação máxima de gorduras (p = 0,038) quando comparados aos não portadores (Trp64Trp). Conclusões: Embora os processos fisiológicos relacionados à lipólise e ao metabolismo de lipídeos sejam complexos, a presença do alelo Arg64 associou-se a menores taxas de FATMAX durante exercício aeróbio, bem como maiores níveis de lipoproteina de baixa densidade em adolescentes. Keywords: Genetic polymorphism, Exercise, Lipid metabolism, Lipolysis, Adolescents, Palavras‐chave: Polimorfismo genético, Exercício, Metabolismo de lipídeos, Lipólise, Adolescentes